Effects of a Tootle-Based Game to Strengthen Children’s Prosocial Behaviors in a Brazilian School Context (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The current study evaluated the effects of a gamified project utilizing tootles on the incidence and prevalence of pro- and antisocial behaviors in two classrooms in a public school. Children and teachers were encouraged to write tootles and glue them in a mural according to game challenges. Each tootle resulted 1 point to the class. If children and teachers achieved the minimum number of tootles during the challenges, other sectors in the city arranged recreative activities to children as celebration. Direct observations from the behavior of 8 children were carried out on a daily basis. Results showed increases in the incidence and prevalence of prosocial behavior in both classrooms, with a more salient effect in Class A. Antisocial behaviors remained steady and near to zero. Other prosocial behavior instances were reported in addition to those suggested by them previously. Ultimately, teachers rated the project positively. Limitations and recommendations for replications are then discussed.